2020
DOI: 10.1158/1078-0432.ccr-20-0844
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib and Trastuzumab in HER2-Positive Advanced Breast Cancer: Results from the Phase II SOLTI-1303 PATRICIA Trial

Abstract: Purpose:To assess palbociclib in combination with trastuzumab with or without endocrine therapy in patients with HER2-positive advanced breast cancer.Patients and Methods:PATRICIA is a prospective, open-label, multicenter phase II trial. Patients had received 2–4 prior lines of anti-HER2–based regimens. Treatment consisted of palbociclib 200 mg daily for 2 weeks and 1 week off plus trastuzumab. The study was based on a Simon two-stage design comprising three cohorts: estrogen receptor (ER)-negative (cohort A),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 49 publications
0
75
0
1
Order By: Relevance
“…For example, combinations of trastuzumab or lapatinib with everolimus have demonstrated encouraging antitumor activity in HER2-overexpressing tumors (49)(50)(51)(52). A recent report demonstrated that trastuzumab in combination with palbociclib exhibits promising survival outcomes in trastuzumab pretreated estrogen receptor-positive (ER þ )/HER2 þ advanced breast cancer (53). As a novel HER2 inhibitor, neratinib has demonstrated powerful therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, combinations of trastuzumab or lapatinib with everolimus have demonstrated encouraging antitumor activity in HER2-overexpressing tumors (49)(50)(51)(52). A recent report demonstrated that trastuzumab in combination with palbociclib exhibits promising survival outcomes in trastuzumab pretreated estrogen receptor-positive (ER þ )/HER2 þ advanced breast cancer (53). As a novel HER2 inhibitor, neratinib has demonstrated powerful therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Palbociclib also showed promising results in early‐phase clinical trials, 39 and positive results from a randomized, phase II study were recently published 40 . The PATRICIA trial evaluated the role of palbociclib plus trastuzumab in patients with pretreated HER2+ mBC, both ER‐ (cohort A) and ER+ (cohort B).…”
Section: Cdk4‐6 Inhibition In Her2‐positive Breast Cancermentioning
confidence: 99%
“…Interestingly, 83% of tumours were profiled using PAM50, and luminal disease was significantly associated with longer PFS (HR 0.40, P = .003). Due to the promising survival results observed in this subgroup, study enrolment was stopped prematurely, and a new randomized cohort was opened in this population 40 . The observation that luminal subtype had the greatest benefit from palbociclib is intriguing, considering that a previous work by Prat et al showed that most luminal/HER2+ BC share the same genomic and genetic alterations as luminal/HER2‐ BC, except for HER2 amplification 41 …”
Section: Cdk4‐6 Inhibition In Her2‐positive Breast Cancermentioning
confidence: 99%
“…In a phase 1b/2 trial of ribociclib (continuous dosing, 400 mg per day) plus trastuzumab in heavily pretreated patients with HER2+ MBC, limited clinical activity was observed with a median PFS of 1.33 months 21 . The recently reported phase II SOLTI-1303 PATRICIA trial further supports that the activity of CDK 4/6 inhibitors in HER2+ MBC is greater in patients who are also HR+ 22 .…”
Section: Introductionmentioning
confidence: 78%